2011
DOI: 10.1016/j.janxdis.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms, intimate partner violence perpetration, and the mediating role of shame processing bias

Abstract: Posttraumatic stress disorder (PTSD) may produce internal “threats to the self,” which generate shame. Shame is theoretically and empirically linked to intimate partner violence (IPV) perpetration. We examined relations among PTSD, cognitive processing of shame-relevant information, and IPV perpetration. Forty-seven community participants completed an emotional Stroop task with shame-relevant and neutral words. Stimuli were presented supraliminally (i.e., until vocal response) and subliminally (i.e., below an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 72 publications
3
43
1
Order By: Relevance
“…Because masculine gender role stress has been shown to mediate the link between such fear and men’s perpetration of physical aggression toward their female intimate partners (Jakupcak et al 2002), a similar mechanism is plausible for hegemonic masculine norms. This mechanism is consistent with extant literature which identifies cognitive processing biases as a risk factor for non-alcohol related (Eckhardt, Samper, Suhr, and Holtzworth-Munroe 2012; Persampiere, Poole, and Murphy 2014; Sippel and Marshall 2011) and alcohol-related intimate partner physical aggression (for a review, see Clements and Schumacher, 2010). …”
Section: Introductionsupporting
confidence: 89%
“…Because masculine gender role stress has been shown to mediate the link between such fear and men’s perpetration of physical aggression toward their female intimate partners (Jakupcak et al 2002), a similar mechanism is plausible for hegemonic masculine norms. This mechanism is consistent with extant literature which identifies cognitive processing biases as a risk factor for non-alcohol related (Eckhardt, Samper, Suhr, and Holtzworth-Munroe 2012; Persampiere, Poole, and Murphy 2014; Sippel and Marshall 2011) and alcohol-related intimate partner physical aggression (for a review, see Clements and Schumacher, 2010). …”
Section: Introductionsupporting
confidence: 89%
“…A portion ( n = 12) designed scales or questions exclusively for their investigation. The notable exceptions to this self-report trend were three studies, two of which utilized laboratory-based paradigms to examine implicit shame processing [9,47], and one that measured nonverbal shame through coding of facial expressions [28]. Similarly, posttraumatic stress symptoms were routinely measured with self-report questionnaires such as the PTSD-Checklist [48].…”
Section: Resultsmentioning
confidence: 99%
“…Their difference is further highlighted in what each emotion motivates: guilt may prompt reparative efforts whereas shame may trigger avoidance and withdrawal. While several theoretical models [8,9,10,11] differ on when shame occurs in the sequence of pre-trauma events to post-trauma, they converge on the functional role of shame in PTSD development. Experiencing shame, whether through attributing blame to the self or for one’s symptom presentation after diagnosis with PTSD, prohibits integration of the traumatic memory into one’s identity, thereby preventing recovery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, past research has found that female trauma survivors tend to endorse greater self-blame for the event, greater beliefs that they are damaged or incompetent, and greater beliefs that the world is dangerous, as compared to male trauma survivors (Tolin & Foa, 2002). Additionally, implicit shame-processing bias has been shown to explain the relationship between PTSD symptoms and IPA use, based on the idea that aggression toward the source of expected negative evaluation and rejection may be used to minimize the discomfort produced by these expectations (Sippel & Marshall, 2011). Thus, it may be beneficial for future work to examine other cognitive schemas (e.g., self-esteem, power and control) as mediators of the relationship between trauma and IPA use for both men and women.…”
Section: Discussionmentioning
confidence: 99%